Numerical ranges of operators on normed spaces and of elements of normed algebras - Bonsall, F. F.; Duncan, J. (John), 1938- (London Mathematical Society lecture note series, 1971)
The theory of the numerical range of a linear operator on an arbitrary normed space had its beginnings around 1960, and during the 1970s the subject has developed and expanded rapidly. This book presents a self-contained exposition of the subject as a whole. The authors develop various applications, in particular to the study of Banach algebras where the numerical range provides an important link between the algebraic and metric structures.